In vitro mutagenicity of selected environmental carcinogens and their metabolites in MutaMouse FE1 lung epithelial cells. (5th January 2021) - Hölzl-Armstrong, Lisa; Nævisdal, Andrea; Cox, Julie A; Long, Alexandra S; Chepelev, Nikolai L; Phillips, David H; White, Paul A; Arlt, Volker M
Abstract: Chemicals in commerce or under development must be assessed for genotoxicity; assessment is generally conducted using validated assays (e.g. Tk mouse lymphoma assay) as part of a regulatory process. Currently, the MutaMouse FE1 cell mutagenicity assay is undergoing validation for eventual use as a standard in vitro mammalian mutagenicity assay. FE1 cells have been shown to be metabolically competent with respect to some cytochrome P450 (CYP) isozymes; for instance, they can convert the human carcinogen benzo[ a ]pyrene into its proximate mutagenic metabolite. However, some contradictory results have been noted for other genotoxic carcinogens that require two-step metabolic activation (e.g. 2-acetylaminofluorene and 2-amino-3-methylimidazo[4, 5- f ]quinoxaline). Here, we examined three known or suspected human carcinogens, namely acrylamide, 2-amino-1-methyl-6-phenylimidazo[4, 5- b ]pyridine (PhIP) and 4-aminobiphenyl (4-ABP), together with their proximate metabolites (i.e. glycidamide, N -OH-PhIP and N -OH-4-ABP), to aid in the validation of the FE1 cell mutagenicity assay. Assessments of the parent compounds were conducted both in the presence and absence of an exogenous metabolic activation mixture S9; assessments of the metabolites were in the absence of S9. The most potent compound was N -OH-PhIP -S9, which elicited a mutant frequency (MF) level 5.3-fold over background at 5 µM. There was a 4.3-fold increase for PhIP +S9 at 5 µM, a 1.7-fold increase for glycidamide −S9 at 3.5 mM and a 1.5-fold increase for acrylamide +S9 at 4 mM. Acrylamide −S9 elicited a marginal 1.4-fold MF increase at 8 mM. Treatment with PhIP −S9, 4-ABP ±S9 and N -OH-4-ABP −S9 failed to elicit significant increases in lacZ MF with any of the treatment conditions tested. Gene expression of key CYP isozymes was quantified by RT-qPCR. Cyp1a1, 1a2 and 1b1 are required to metabolise PhIP and 4-ABP. Results showed that treatment with both compounds induced expression of Cyp1a1 and Cyp1b1 but not Cyp1a2 . Cyp2e1, which catalyses the bioactivation of acrylamide to glycidamide, was not induced after acrylamide treatment. Overall, our results confirm that the FE1 cell mutagenicity assay has the potential for use alongside other, more traditional in vitro mutagenicity assays.